TRANSLANGUAGING PRACTICES IN EFL CLASSROOMS: TEACHERS’ PERSPECTIVE - Fabelia Indah Putri; Irfan Rifai (English Journal Literacy Utama, 2021)
This study is centered on exploring the teachers' perspective towards translanguaging practices in EFL classrooms. This study is framed within a qualitative case study involving four English teachers from two high schools in Sidoarjo, East Java. In order to understand the subjects' perspectives, personal interviews were utilized. The data having been collected, it were transcribed verbatim and analyzed thematically. The current study's findings show that teachers practiced translanguaging mainly when they explained the materials, such as grammar. In this sense, the sole motivation of using translanguaging is that grammar is complex and explaining in English is far more complicated. In addition, teachers also practiced translanguaging when they managed the classroom, showing shared cultural values. Further analysis showed that translanguaging helps teachers achieve their goals, and one of the goals is helping their students understand the materials explained in English better. The results of this study are expected to be advantageous for the teachers to be aware of the importance of translanguaging practices in the EFL classroom.